2019
DOI: 10.1021/acs.iecr.8b03982
|View full text |Cite
|
Sign up to set email alerts
|

Improving Selectivity to 1,3-Propanediol for Glycerol Hydrogenolysis Using W- and Al-Incorporated SBA-15 as Support for Pt Nanoparticles

Abstract: Tungsten and aluminum were directly incorporated into SBA-15 via one-step synthesis method under an acidic medium. The W-and Al-incorporated SBA-15 was applied as support for Pt nanoparticles to catalyze glycerol hydrogenolysis toward 1,3-propanediol. A combination of the characterization techniques showed that the tungsten and aluminum were incorporated into SBA-15 homogeneously, and the platinum nanoparticles could be uniformly dispersed on the modified-SBA-15. The catalytic performance of Pt-loaded SBA-15 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 69 publications
1
40
1
1
Order By: Relevance
“…Driven by the great potential for practical applications, this reaction has been intensively studied . So far, it has been established that a noble metal in combination with an oxophilic metal oxide, typically like Ir−ReO x, Rh−ReO x and Pt−WO x , is effective for the formation of 1,3‐PDO. In comparison with ReO x , WO x offers the advantage of better leaching‐resistance and lower cost, therefore shows greater potential for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Driven by the great potential for practical applications, this reaction has been intensively studied . So far, it has been established that a noble metal in combination with an oxophilic metal oxide, typically like Ir−ReO x, Rh−ReO x and Pt−WO x , is effective for the formation of 1,3‐PDO. In comparison with ReO x , WO x offers the advantage of better leaching‐resistance and lower cost, therefore shows greater potential for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The FT‐IR spectra of the parent SBA‐15 (a) nPrCl‐SBA‐15 (b), guanine‐SBA‐15 (c) and La@guanine@SBA‐15 (d) are shown in Figure . Considering SBA‐15, the present bands at about 1082 cm −1 , 807 cm −1 and 462 cm −1 attributed to the vibration modes of asymmetric stretching, symmetric stretching and bending Si‐O–Si . The presence of hydroxyl groups is well seen at 3443 cm −1 (Figure (a)) .…”
Section: Resultsmentioning
confidence: 85%
“…Also, it was found that the position of the d 100 peak in the catalyst shifted to lower values, which are due to the shrinking pore size, and reduced the order of homogeneity of the pores in comparison to SBA‐15. This may correspond to the re‐condensation reactions of the silica with lanthanum nanoparticles in the pore channel …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations